Acute noncardiogenic pulmonary edema after neostigmine administration during the recovery period of general anesthesia: A case report. Issue 21 (May 2018) - Zhang, Wenjing; Ning, Cong; Zhao, Guoqing; Su, Zhenbo
Abstract: Rationale: Acute non-cardiogenic pulmonary edema (ANPE) is a rare but challenging complication which occurs during the perioperative period, mainly before and after the extubation in the course of the recovery period of general anesthesia. It is characterized by increased fluid in extravascular pulmonary spaces, preventing gas exchange and further resulting in respiratory failure. Patient concerns: A 12-year-old boy who had undergone island skin flap in the right upper limb and who developed a unilateral pulmonary edema after the administration of neostigmine during the recovery period of general anesthesia. The neostigmine was administered to reverse neuromuscular block. Diagnoses: Acute non-cardiogenic pulmonary edema. Interventions: The patient was transferred to intensive care unit (ICU) and treated with mechanical ventilation (controlled mode ventilation pattern, CMV) and other supportive treatment. Outcomes: The oxyhemoglobin saturation of the patient returned to the normal level with symptoms and signs of ANPE significantly alleviated. The mechanical ventilation was withdrawn by the fourth day, and no sequela of vital organs was observed. Lessons: Although neostigmine is widely used for recovery from neuromuscular block and exhibits satisfactory effect in most cases, there is a potential risk of ANPE in some cases, which is rare but potentially fatal and could affect the patient outcomes. Therefore, it is necessary for anesthetists to closely monitor the vital signs of patients after administration of neostigmine in the perioperative period.